Phosphorylation of Extracellular Proteins in Acinetobacter baumannii in Sessile Mode of Growth - Massier, Sébastien; Robin, Brandon; Mégroz, Marianne; Wright, Amy; Harper, Marina; Hayes, Brooke; Cosette, Pascal; Broutin, Isabelle; Boyce, John D.; Dé, Emmanuelle; Hardouin, Julie (Frontiers in Microbiology, 2021)
Acinetobacter baumannii is a problematic nosocomial pathogen owing to its increasing resistance to antibiotics and its great ability to survive in the hospital environment, which is linked to its capacity to form biofilms. Structural and functional investigations of post-translational modifications, such as phosphorylations, may lead to identification of candidates for therapeutic targets against this pathogen. Here, we present the first S/T/Y phospho-secretome of two Acinetobacter baumannii strains, the reference strain ATCC 17978 and the virulent multi-drug resistant strain AB0057, cultured in two modes of growth (planktonic and biofilm) using TiO2 chromatography followed by high resolution mass spectrometry. In ATCC 17978, we detected a total of 137 (97 phosphoproteins) and 52 (33 phosphoproteins) phosphosites in biofilm and planktonic modes of growth, respectively. Similarly, in AB0057, 155 (119 phosphoproteins) and 102 (74 phosphoproteins) phosphosites in biofilm and planktonic modes of growth were identified, respectively. So, for both strains, the biofilm mode of growth showed a higher number of phosphosites and phosphoproteins compared to planktonic growth. Several phosphorylated sites are localized in key regions of proteins involved in either drug resistance (β-lactamases), adhesion to host tissues (pilins) or protein secretion (Hcp). For example, in Hcp, protein essential for type VI secretion system-mediated interbacterial competition, site-directed mutagenesis showed that 4 of the modified residues are essential for formation of a fully active type 6 secretion system.